2022
DOI: 10.1155/2022/8958865
|View full text |Cite|
|
Sign up to set email alerts
|

Artificial Intelligence-Based Recommendation and Application of Public Services in Smart Cities

Abstract: With the promotion and application of information technology, smart cities based on artificial intelligence have become the best choice for the government to solve urban problems, connect urban citizens, and provide quality public services. From the initial information city and digital city to the current smart city, the construction of smart cities has undergone profound changes with five major characteristics: big data, intelligence, innovation, interaction, and integration, and Internet giants have emerged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…These elements, by their very design, can be susceptible to breaches, even by the smallest snippets of malicious code [57][58][59]. Consequently, information security shifts beyond the individual user's realm and emerges as a communal imperative within the smart city landscape [60][61][62]. Moreover, the escalating intricacy of the system's network infrastructures, magnified by digital communication, interconnected devices, and diverse network architectures, inevitably poses heightened security challenges [1,[63][64][65][66][67].…”
Section: Smart Cities and Information Securitymentioning
confidence: 99%
“…These elements, by their very design, can be susceptible to breaches, even by the smallest snippets of malicious code [57][58][59]. Consequently, information security shifts beyond the individual user's realm and emerges as a communal imperative within the smart city landscape [60][61][62]. Moreover, the escalating intricacy of the system's network infrastructures, magnified by digital communication, interconnected devices, and diverse network architectures, inevitably poses heightened security challenges [1,[63][64][65][66][67].…”
Section: Smart Cities and Information Securitymentioning
confidence: 99%
“…hd . The neuron output is computed using (2). Here, the connection weight of th c neuron and in ( 1) th j − hidden layer, there are 1 j d − neurons.…”
Section: Hybrid Rule-based Deep Neural Networkmentioning
confidence: 99%
“…The Internet of Things has altered people's lifestyles [1]. Smart cities are being developed, including facilities such as automated railways, smart autos, automated parking, and smart lighting [1], [2]. Concerns have been raised about privacy and the misuse of technology in smart homes [3].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%